Implementing the sharing economy in the context of achieving sustainable economic development in Russia - Mikhail Vladimirovich Khachaturyan; Evgeniia Valeryenva Klicheva (Journal of Innovation & Knowledge (JIK), 2025)
The sharing economy has gained significant attention both internationally and in Russia. This involves the integration of innovative technologies into national economic systems to promote economic growth and environmental sustainability. The introduction of sharing economy principles has led to sudden, and sometimes unexpected changes in the standards and regulations governing the operations of national economies and their sectors. This has raised concerns among academics and businesses regarding the accuracy and completeness of analyses conducted to assess the full range of benefits and drawbacks associated with these new models of economic behaviour. In this context, this study aims to address the lack of theoretical and empirical understanding of management science by conducting a quantitative analysis of the impact of the sharing economy on Russia's path to sustainable economic growth between 2010 and 2023. Using the quantile autoregressive distributed lag (QARDL) method, a common approach in management research, we consider factors such as population growth, unemployment rates, energy prices, and inflation rates. The findings suggest that the sharing economy has a positive impact on sustainable development across all segments, although its effect on energy efficiency is stronger in higher segments. Based on these findings, we argue that growth of the sharing economy, both within Russia and globally, can promote energy efficiency and sustainable development. Furthermore, the study emphasises the significance of the economic aspect of shared consumption, and recommends that the Russian government adopt legal and administrative measures to promote it. These measures can contribute in achieving sustainable development goals and improving energy efficiency within the Russian economy.
Keywords: 650; Sharing economy; Energy efficiency; Sustainable development; Russian economy; National economy; Incentives